2018
DOI: 10.1002/advs.201800510
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine‐Modified Black Phosphorous Nanocapsule with Enhanced Stability and Photothermal Performance for Tumor Multimodal Treatments

Abstract: As a novel 2D material, black phosphorus (BP) nanosheets are considered as a promising candidate for drug delivery platform for synergistic chemo/photothermal therapy. However, the intrinsic instability of bare BP poses a challenge in its biomedical applications. To date, some strategies have been employed to prevent BP from rapid ambient degradation. Unfortunately, most of these strategies are not suitable for the drug delivery systems. Here, a simple polydopamine modification method is developed to enhance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
335
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 475 publications
(345 citation statements)
references
References 49 publications
3
335
0
Order By: Relevance
“…The construction of co‐delivery systems renders greater therapeutic effect compared to a single treatment modality. Even though numerous studies have been reported in this field, the lack of an effective method to fine‐tune the ratio of co‐loaded therapeutic agents has obstructed successful cancer treatment. There are three popular strategies employed for the co‐delivery of PSs with prodrugs: i) the covalent conjugation of a PS to a prodrug, ii) grafting the PS or drug with a carrier, and loading the other component as the cargo, iii) co‐loading the two components within a carrier, such as polymers and inorganic porous nanoparticles .…”
Section: Methodsmentioning
confidence: 99%
“…The construction of co‐delivery systems renders greater therapeutic effect compared to a single treatment modality. Even though numerous studies have been reported in this field, the lack of an effective method to fine‐tune the ratio of co‐loaded therapeutic agents has obstructed successful cancer treatment. There are three popular strategies employed for the co‐delivery of PSs with prodrugs: i) the covalent conjugation of a PS to a prodrug, ii) grafting the PS or drug with a carrier, and loading the other component as the cargo, iii) co‐loading the two components within a carrier, such as polymers and inorganic porous nanoparticles .…”
Section: Methodsmentioning
confidence: 99%
“…c) Schematic illustration of BP‐D@PDA for cancer therapy. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: D Nanomaterials For Ptt‐based Synergistic Therapymentioning
confidence: 99%
“…To improve the efficiency of PTT‐synergized chemotherapy, ligands can be attached to the 2D nanomaterials for active targeting. Zeng et al . employed BP nanosheets modified with NH 2 ‐PEG‐Apt as a drug delivery platform, which showed improved stability and targeting ability (Figure c).…”
Section: D Nanomaterials For Ptt‐based Synergistic Therapymentioning
confidence: 99%
“…[39,40] Compared to the traditional inorganic/organic nanoparticles, MOF offers adjustable structural and chemical composition at the molecular level together with tunable porosity and chemical stability, which can as transport vehicles for the delivery of imaging agents and biologically active molecules realize accurate diagnosis and treatment of tumors. [45] 2D nanosheets with large surface area, unique physical, and chemical properties have been widely used as theranostic agents for cancer treatment, such as graphene, transition metal dichalcogenides, black phosphorus, [46][47][48] boron nanosheets, [42] accomplishing multimodal imaging-guided synergistic treatment. [43] Porphyrin-based MOF that have been developed so far for potential PDT outcome, however, almost all of them are compounded with other nanoparticles to form new compounds for synergistic treatment (such as PDT-PTT, PDT-Radiation therapy), [44] the complex structures would reduce the clinical medical value.…”
Section: Doi: 101002/advs201900530mentioning
confidence: 99%